Bibliocounseling training as an effort to improve emotional wellness of the elderly - Muya Barida; Siti Partini Suardiman; Dessy Pranungsari; Intan Puspitasari; Dian Ari Widyastuti; Sri Tutur Martaningsih (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2025)
Emotional wellness for the elderly is very important to live a peaceful life. There are many ways to improve the wellness of the elderly through a series of social support activities, one of which is bibliocounseling. This community service activity aims to improve emotional wellness through bibliocounseling. Community service activities are carried out for the elderly in the Special Region of Yogyakarta and Central Java. Participants consisted of 60 elderly people. Through community service activities with Bibliocounseling, it is hoped that the emotional wellness of the elderly can increase. The results of filling in the emotional wellness scale show that the older the individual, the higher their emotional wellness. However, when Bibliocounseling was carried out, the elderly admitted that they still experienced bad emotional conditions such as anger, sadness, and disappointment. Through this bibliocounseling training, the elderly felt happy and committed to changing habits that strengthen emotional wellness